Learning Media Based on the Sun Bear Educational Module on Indonesian Biodiversity Material - Muluk, Verena Suryati; Rambitan, Vandalita M.M.; Palenewen, Evie; Akhmad, Akhmad; Candra, Krishna P.; Tindangen, Makrina (Newinera Publisher, 2025)
This study aims to develop a learning media based on a honey bear education module used in the Indonesian biodiversity material for seventh-grade junior high school students. The background of this study is based on the importance of strengthening biodiversity material through a contextual approach that includes environmental conservation values, especially the protection of endemic species such as the honey bear (Helarctos malayanus). This study uses the ADDIE development model which includes five stages, namely: analysis, design, development, implementation, and evaluation. The research instruments include expert validation sheets (material, media, and language), science teacher validation sheets, student response questionnaires, and learning outcome tests (pre-test and post-test). The limited trial subjects were 25 seventh-grade students at a junior high school in Balikpapan. The results of the material expert validation showed a feasibility percentage of 78.67%, media expert validation of 56.36%, and validation by science teachers of 81.33%. The module was declared feasibility after being revised based on input from experts. The effectiveness test results using a paired t-test showed a significance value of 0.033 (p < 0.05), which means there is a significant difference between student learning outcomes before and after using the module. Furthermore, student responses to the module showed a high level of interest in the content and presentation of the material, as well as an increased awareness of the importance of biodiversity conservation. Thus, this sun bear education module has proven to be feasible and effective for use in science learning on biodiversity material.